The Swot Analysis Of Sharia Fintech Potential In Indonesia: Nvivo Approach Study And Literature Review - Faris, Sukron; Slamet, Slamet; Prajnawati, Maretha Ika; Bagaskara, Doni Yusuf (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2024)
This study aims to determine the SWOT analysis of the potential of Sharia Fintech in Indonesia using the NVivo approach. This research uses qualitative methodology using the NVivo approach and literature review. "Data analysis techniques include: (1) mapping the number of news article codes based on SWOT analysis, namely (strengths, weaknesses, opportunities, and threats), around "Fintech Sharia" using NVivo 14 software; (2) mapping the results of visualization with hierarchical diagrams and testing the correlation of relationships between media articles using SWOT Analysis; (3) map the research topic with Worldcloud or a collection of words that are often discussed in media articles, and (4) Testing the significant value between media articles to determine the size or size of a correlation around the topic of "Sharia Fintech." The results of this study show that the topics often discussed in media articles about Fintech Sharia are strengths and opportunities. Topics rarely discussed by media articles about Fintech Sharia are weaknesses and threats.